2012
DOI: 10.14350/rig.30097
|View full text |Cite
|
Sign up to set email alerts
|

Semejanza florística entre los bosques de Abies religiosa (H.B.K.) Cham. & Schltdl. de la Faja Volcánica Transmexicana

Abstract: Se analizó la semejanza en la composición de familias, géneros y especies de plantas vasculares de los bosques de oyamel de la Faja Volcánica Transmexicana, los datos se obtuvieron a partir de la revisión bibliográfica en 12 localidades. Con esta información se estimó la semejanza florística entre los sitios mediante métodos de clasificación y ordenación. La flora de estos bosques contiene 76 familias, 222 géneros y 510 especies. Fue posible detectar patrones en la composición y estructura de los bosques de oy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
0
4
0
16
Order By: Relevance
“…La considerable diversidad taxonómica del área de estudio (B = 210.33 especies/km 2 ), permite señalar que es más diversa que los bosques citados por Sánchez-González et al (2005) para la FVT, los cuales se desarrollan a elevaciones entre 2,500 y 3,500 m, pero es menor a la del BMM de la SMS (Lozada et al, 2003;Padilla et al, 2008;Cuadro 5). Por su parte, estudios realizados en Eloxochitlán y Tlahue-…”
Section: Discussionunclassified
“…La considerable diversidad taxonómica del área de estudio (B = 210.33 especies/km 2 ), permite señalar que es más diversa que los bosques citados por Sánchez-González et al (2005) para la FVT, los cuales se desarrollan a elevaciones entre 2,500 y 3,500 m, pero es menor a la del BMM de la SMS (Lozada et al, 2003;Padilla et al, 2008;Cuadro 5). Por su parte, estudios realizados en Eloxochitlán y Tlahue-…”
Section: Discussionunclassified
“…This is due to the environmental heterogeneity presented by these forests and to their complex biogeographic history. With regard to the floristic composition of Abies forests, Sánchez-González et al (2005) compared exclusivity across 12 sites on the Trans-Mexican Volcanic Belt and found that only 8 % of the species were shared with the majority of the sites, a value that should not be minimized since some of these are abundant species which define the forest structure. In the MBBR, grasslands are the vegetation type with the third highest number of exclusive species.…”
Section: Flora Of the Monarch Butterfly Biosphere Reservementioning
confidence: 99%
“…The floristic affinities in the flora of the MBBR are not easily compared, since the categories of geographic affinities often differ among biogeographic studies. In this sense, Sánchez-González et al (2005) found that 32 % of the species of the Abies forest of the mountain Tláloc (Estado de México) are endemic to Mexico, and 31 % extend to Central America. The Abies forests in our study site has a similar pattern, as these distribution categories represent 39.2 and 21.9 %, values that are also similar to those found for the entire flora (Table 4).…”
Section: Flora Of the Monarch Butterfly Biosphere Reservementioning
confidence: 99%
“…et Cham., se distribuye principalmente en el Parque Nacional Cofre de Perote (PNCP) (Sánchez-Velásquez, Pineda-López, & Henández, 1991) y en el Pico de Orizaba (Rzedowski, 2006), los cuales forman parte del programa de las 60 montañas prioritarias (Zúñiga, PinedaLópez, & Becerra, 2008). Los rodales de A. religiosa son ecosistemas frágiles, cubren menos de 0.1 % de la superficie del país (Sánchez-González, López-Mata, & Granados-Sánchez, 2005) y se ven amenazados por el cambio climático (VillersRuíz & Trejo-Vázquez 1998), la contaminación del aire (Saavedra-Romero, Alvarado-Rosales, Vargas-Hernández, & Hernández-Tejeda, 2003), los incendios forestales (Ángeles-Cervantes & López-Mata 2009) y el cambio de uso del suelo (Pedraza-Pérez, Hoyos-Ramírez, & Álvarez-Oceguera, 2009). Además, la especie presenta bajo porcentaje de germinación con alto porcentaje de semillas vanas (Nieto de Pascual-Pola, Musálem, & Ortega-Alcalá, 2010).…”
Section: Introductionunclassified
“…et Cham., is mainly found in the Cofre de Perote National Park ( CPNP) (Sánchez-Velásquez, Pineda-López, & Henández, 1991) and the Pico de Orizaba (Rzedowski , 2006), which are part of the program of the 60 priority mountains (Zúñiga, PinedaLópez, & Becerra, 2008). The stands of A. religiosa are fragile ecosystems covering less than 0.1 % of the surface of the country (Sánchez-González, López-Mata, & Granados-Sánchez, 2005) The structure of a stand is determined by the composition and size distribution of the species, and is useful for explaining the growth forms of the stands (Odum, 1985). Consequently, studying and understanding the structure of forest stands constitutes a premise to achieve proper management (Urbieta, 2009) for conservation and restoration of these stands.…”
Section: Introductionmentioning
confidence: 99%